Analisa Perhitungan Pathloss Propagasi Gelombang Radio Outdoor Menggunakan Model Hata dan Model Cost 231 Pada Jaringan 3G Telkomsel Lhokseumawe - Amir D; Naziruddin; Jamaluddin; Ariefin; Halim Saini (Jurnal Serambi Engineering, 2024)
The problem that arises in wireless communications is how to predict the transmission channel attenuation between Tx transmitters and Rx receivers that have different channel characteristics. This research explains the results of comparing the Hata empirical model with the Cost 231 model. The empirical model is a prediction model for radio wave attenuation used by engineers in the field without the use of experimental equipment. The aim of this research is to determine the accuracy of the calculation results in the two models. Three locations were used as research samples, namely Darussalam Road, Samudera Baru Road and Gudang Baru Road. The third locations have different distances and BTS. The standard deviation shows the amount of deviation from the average distribution of the predicted data group. Based on the prediction results at the three locations, the Cost 231 model produces larger predicted pathloss calculations compared to the Hata model, the average value of the pathloss prediction of the Cost 231 model is 260.47 dB and the Hata model is 196.46 dB, the difference between the two calculation results is 64.01. The empirical Cost 231 model gives a standard deviation of the mean distribution of 13.59, while the Hata model gives a standard deviation of 0.56 of the mean distribution of the calculated values.